EXPERT SYSTEM TO DIAGNOSE BOTTLE DISEASE USING FUZZY LOGIC METHOD - Ayu Handari; Muhammad Syahputa Novelan; M. Donni Lesmana Siahaan (Sean Institute, 2022)
One of the most important parts of handling livestock health, especially cattle, is observing livestock suspected of being sick through examination. But unfortunately, the knowledge of the breeders regarding the diseases in cattle that should still be handled by the farmers themselves must be handled by livestock experts as experts in handling cattle diseases. Meanwhile, the number of cattle experts is an experts is still small and the costs incurred by farmers for consulting the health of their livestock are also not small. Experts systems are a branch of AI (Artificial Intelegent) which makes extensions for specialization of knowledge to solve a problem on Human Expert. Human Expert is an expert in a certain field of science. Tsukamoto’s Fuzzy Logic Method is a method that focuses on rules in the form of IF-THEN represented by fuzzy sets with monotonous membership function, as well as criteria and rules used to determine the final result, at the same time a behavioral model was developed using data flow diagrams (UML) and flowcharts are graphical depictions of the steps and sequences of procedures of a program supported by and process specifications which are specifications of the functional requirements of the system.